PENENTUAN KOMPONEN KUALITAS DAN BAHAN BAKU OPTIMAL PRODUK KECAP ORGANIK BERBASIS OFF LINE QUALITY CONTROL (DETERMINATION ON OPTIMUM QUALITY COMPONENTS AND RAW MATERIALS OF ORGANIC SOY SAUCE BASED ON OFF LINE QUALITY CONTROL) - Setiawati, Bernadetta Budi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
Organic Soy Sauce quality didn't fit with the producer's quality expectation, when the organic soy sauce didn't give uniform characteristics such as taste, color and viscosity. It led to the consumer's unsatisfaction. Efforts for the quality improvement should be conducted in order to meet the consumer's satisfaction. This research aimed to determine optimum quality components and raw materials of organic soy sauce which met consumer's satisfaction based on off-line control. The Taguchi method characterized by the off-Line Quality Control was applied to improve quality or processes. Taguchi introduced an integrated design method using Orthogonal Matrix as a supporting tool in experiments and in analyzing results and using Signal to Noise Ratio (SNR) to determine Factor Effect and Analysis of Variance as well. Based on consumer's response tests on taste, color and viscosity, the research's results showed that the optimum quality component of taste, color and viscosity with a value of the SNR factor effect of 11.51; 10.79 and 10.96 and with an average value of consumer's satisfaction level of 4.17 ; 3.73 and 4.03 from maximum value of 5.00. These values contributed the determination of the following components and process such as: black soybean variety originated from Bambanglipuro Sub-District, moromi processing time of 4 weeks, a total of moromi of 320 mLs, spices weight of 6 grams, coconut sugar weight of 700 grams, water of 465 mLs, coconut sugar of black color and fermentation time of 8 minutes. Keywords: